Decision-making in artificial nutrition and hydration: Ethical and legal considerations for minors and incapable patients - Karaboue, Karidia (Progress in Nutrition, 2025)
The complex issues surrounding the administration of Artificial Nutrition and Hydration (ANH) in cases involving minors or individuals incapable of understanding and willing are examined, focusing on who should make the relevant decisions and the ethical, deontological, and legal aspects involved. Challenges in obtaining informed consent from minors and incapable individuals are highlighted, emphasizing the importance of considering the best interest of the patient. Advocating for a therapeutic alliance, the involvement of the minor, the guardian, and the physician in the decision-making process is recommended to ensure the patient's rights and dignity are respected. The need for a multidisciplinary approach in evaluating the benefits and risks of ANH is addressed, stressing the principles of proportionality and beneficiality to prevent unnecessary suffering. The role of the healthcare provider in navigating these ethical dilemmas and the importance of collaboration among medical staff, legal guardians, and families are underscored to ensure ethically and clinically appropriate care.